2018
DOI: 10.1007/s10971-018-4826-4
|View full text |Cite
|
Sign up to set email alerts
|

Sintering of aerogels for glass synthesis

Abstract: Silica glasses can be synthesized by sintering silica aerogels at temperatures ranging from 900 to 1200°C, i.e., close to half the temperatures used for glass melting. The heat treatment can be tailored to obtain either fully densified or porous glass. This paper describes the different steps of the transformation of aerogels into glass along with the textural and microstructural transformations. Different types of information are analyzed: variations in dimensional shrinkage and the apparent density as a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Sintering identification was obtained by studying the kinetics of shrinkage. In a previous work [9,11], we have shown that both mechanisms are responsible for sintering of classical silica aerogels. At low temperatures, the low sintering is due to a slow diffusion process (500 to 700° C) [27] whereas at temperatures above 1000 ° C, the sintering is related to a viscous flow.…”
Section: Synthesis Of Silica Glass From Composites Aerogelsmentioning
confidence: 82%
See 3 more Smart Citations
“…Sintering identification was obtained by studying the kinetics of shrinkage. In a previous work [9,11], we have shown that both mechanisms are responsible for sintering of classical silica aerogels. At low temperatures, the low sintering is due to a slow diffusion process (500 to 700° C) [27] whereas at temperatures above 1000 ° C, the sintering is related to a viscous flow.…”
Section: Synthesis Of Silica Glass From Composites Aerogelsmentioning
confidence: 82%
“…The "aerogel" is a solid material, amorphous and highly porous (80-99% porosity) [5] that can be transformed into silica glasses by a sequence of sintering treatments [9,10,11]. Depending on the duration of the heat treatment, porosity is progressively eliminated [11].…”
Section: ) Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are currently many applications of aerogels, such as catalysts [ 2 ], insulators [ 3 ], sensors [ 9 ] environmental [ 10 ] and biomedical applications [ 11 , 12 ], etc., and the potential uses of these materials are even larger if one considers the aerogel as a precursor. Through heat treatments, the silica aerogels can indeed be sintered into silicate glasses and glass ceramics [ 13 , 14 ]. However, these porous materials can also be used as a matrix for the synthesis of multi-phase materials, doped materials, or composites.…”
Section: Introductionmentioning
confidence: 99%